Hospitality Towards People with Mental Illness in the Church: a Cross-cultural Qualitative Study - Lehmann, Curtis S.; Whitney, William B.; Un, Jean; Payne, Jennifer S.; Simanjuntak, Maria; Hamilton, Stephen; Worku, Tsegamlak; Fernandez, Nathaniel A. (2022)
Mental illness is a prevalent concern that affects Christian churches in North America in significant ways. Previous studies on the relationship between mental illness and the church have found that beliefs and practices within the church can contribute to stigma towards people with mental illness. Yet, the typical experience of people with mental illness who attend church has been found to be positive, suggesting that there are considerable resources within the church for supporting those who experience mental health problems. One such resource is the concept of hospitality, which promotes a sense of belonging for those with mental illness in the church. This qualitative study advances the construct of hospitality as a helpful paradigm for addressing mental health needs within the church, capturing perspectives and practices that are currently in place or seen as necessary by church attendees. The study methodology also emphasized the need to incorporate cultural considerations that are appropriate for the racial and ethnic make-up of particular churches. Semistructured focus group interviews were conducted with participants from eight churches that were either predominantly African American, Asian American, Latinx, or multi-ethnic. Findings resulting from content analysis of transcripts indicated that hospitality was a broadly helpful construct for addressing mental health concerns in the church, though some cultural differences existed in the understanding and application of hospitality. Both the interface of the findings with the existing scholarly literature and the relevance of findings for church leaders are discussed.
Keywords: Christianity; Culture; Hospitality; Mental Health; Mental Illness; Stigma